The synthesis of 4, 6-diaryl-2-pyridones and their bioactivation in CYP1 expressing breast cancer cells. Issue 11 (1st June 2019) - Ruparelia, Ketan C.; Lodhi, Sabahat; Ankrett, Dyan N.; Wilsher, Nicola E.; Arroo, Randolph R.J.; Potter, Gerard A.; Beresford, Kenneth J.M.
Graphical abstract: Abstract: As part of a programme to develop anticancer prodrugs which are activated by cytochrome P450 (CYP)1B1, a library of 4, 6-diaryl-2-pyridones was synthesised in yields of 6–60% from the corresponding chalcones. A number of these derivatives showed promising antiproliferative activities in human breast cancer cell lines which express CYP1B1 and CYP1A1, while showing little toxicity towards a non-tumour breast cell line with no CYP expression. Metabolism studies provided evidence supporting the involvement of CYP1 enzymes in the bioactivation of these compounds.